Analysis of the Accounting Information System for Pharmaceutical Inventory at the Gonting Malaha Village Health Center, Asahan Regency - Sihombing, Amira Salsabila Afra; Nurwani, Nurwani; Harmain, Hendra (UNIVERSITAS PAKUAN, 2024)
Examining how the Gonting Malaha Village Health Center in Kab. Sharpening keeps track of their medication inventory is the primary goal of this study. Primary data is the source for this study. Observation, interviews, documentation, and questionnaires were used to gather this study data at the research sites. According to the study's findings, the Gonting Malaha Village Health Center's Accounting Information System is poorly implemented. In contrast, the Gonting Malaha Village Health Center only uses manual processes for keeping track of medication supplies and computations. Despite knowing that the system regulates all ongoing activities, the Gonting Malaha Village Community Health Center has not installed an accounting information system. This is due to the fact that the center's operations continue to run smoothly without the system. Unfortunately, due to network issues, the Gonting Malaha Village Community Health Center had to rely on manual computations and record keeping.